Oligoclonal expansion of HIV-specific cytotoxic CD8 T lymphocytes in the skin of HIV-1-infected patients with cutaneous pseudolymphoma. - Bachelez, H (1998)
A massive infiltration of the skin by activated CD8+ T lymphocytes involving both the dermis and the epidermis has been found in HIV-1-infected patients presenting with a chronic skin rash. We characterized the T cell receptor (TCR) BV-BJ junctional diversity of the skin-infiltrating lymphocytes (SILs) in four patients. The SILs expressed a limited set of TCRBV gene segments. Complementarity determining region 3 length analysis further emphasized their oligoclonality, suggesting that antigen stimulation might be responsible for the cutaneous T cell expansion. Furthermore, independent skin biopsies obtained from the same individual were shown to harbor distinct T cell repertoires, possibly reflecting the spatial heterogeneity of the antigenic stimuli. The CD8+ cytotoxic T lymphocyte (CTL) lines isolated from the skin rash in one patient exhibited a specific, class I MHC-restricted cytotoxic activity against HIV-1 Gag- and Pol-expressing target cells, whereas CTL lines derived from the skin lesions of a second patient were shown to be predominantly Env-specific. Taken together, these data demonstrate the infiltration of HIV-specific CTLs in the skin of HIV-infected patients, and suggest that in addition to their known role in controlling the retroviral infection, these CTLs may also be involved in the pathogenesis of cutaneous inflammatory disorders occurring during the course of HIV infection.